2000
DOI: 10.1177/104687810003100112
|View full text |Cite
|
Sign up to set email alerts
|

Learning Sustainable Development with a New Simulation Game

Abstract: This new simulation game, the authors'first, has been created to introduce discipline-related concepts to a wider audience. The authors set out to create a game that would reduce an abstract concept to its basic components and present it within a frame, with the intent to capitalize on the benefits of gaming and simulation. The result of this creative effort is a card game called LEARNING SUSTAINABLE DEVELOPMENT (LSD).This game is intended to create awareness to and explore attitudes toward environmental conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 7 publications
1
20
0
1
Order By: Relevance
“…The games assist students make decisions in a multidimensional environment, * Problem-based: These games allow students to try several approaches depending on the assumptions made. [17] Business ethics Computer based Problem -based [18] Child development Non-computerized Mini-case [19] Interviewing skills Non-computerized Exercise-based [20] Laboratory management Computer based Drill and exercise [21] Medical Computer based Problem-based HEART-SENSE Game [22] Medical Computer based Drill-based Spectrum game [23] Physics Computer based Drill-based [25] Physics Computer based Problem-based Frantic Physics [24] Physics and calculus Computer based Drill-type Tic-Tac-Toe game [24] Mathematics Computer based Exercise-based [37] Computer security Computer based Drill-based SimSE [39] Software engineering Computer based Mini-case based SESAM [40] Software engineering Computer based Mini-case based [41] Software engineering Computer based Mini-case based Project Manager [42] Information systems Computer based Mini-case based KM QUEST [43] Information systems Computer based Problem-based [38] Computer protocols Non-computerized Drill-based MagicBlocks [11] Digital logic Computer based Drill-based Konane [44] Artificial intelligence Non-computerized Drill-based Industrial Waste game [70] Environmental engineering Non-computerized Exercise-based Educational water quality management game [6] Environmental engineering Computer based Problem-based Learning Sustainable Development [13] Environmental engineering Non-computerized Exercise-based Internet-based Interactive Construction Management Learning System [32] Civil engineering Computer based Drill-based [33] Civil engineering Computer based Problem-based [12] Engineering graphics Computer based Drill-based [4] Engineering mechanics Computer based Drill-based [54] System dynamics Computer based Problem-based [50] Thermodynamics Computer based Drill-based [51] Thermodynamics Computer based Drill-based …”
Section: Discussionmentioning
confidence: 99%
“…The games assist students make decisions in a multidimensional environment, * Problem-based: These games allow students to try several approaches depending on the assumptions made. [17] Business ethics Computer based Problem -based [18] Child development Non-computerized Mini-case [19] Interviewing skills Non-computerized Exercise-based [20] Laboratory management Computer based Drill and exercise [21] Medical Computer based Problem-based HEART-SENSE Game [22] Medical Computer based Drill-based Spectrum game [23] Physics Computer based Drill-based [25] Physics Computer based Problem-based Frantic Physics [24] Physics and calculus Computer based Drill-type Tic-Tac-Toe game [24] Mathematics Computer based Exercise-based [37] Computer security Computer based Drill-based SimSE [39] Software engineering Computer based Mini-case based SESAM [40] Software engineering Computer based Mini-case based [41] Software engineering Computer based Mini-case based Project Manager [42] Information systems Computer based Mini-case based KM QUEST [43] Information systems Computer based Problem-based [38] Computer protocols Non-computerized Drill-based MagicBlocks [11] Digital logic Computer based Drill-based Konane [44] Artificial intelligence Non-computerized Drill-based Industrial Waste game [70] Environmental engineering Non-computerized Exercise-based Educational water quality management game [6] Environmental engineering Computer based Problem-based Learning Sustainable Development [13] Environmental engineering Non-computerized Exercise-based Internet-based Interactive Construction Management Learning System [32] Civil engineering Computer based Drill-based [33] Civil engineering Computer based Problem-based [12] Engineering graphics Computer based Drill-based [4] Engineering mechanics Computer based Drill-based [54] System dynamics Computer based Problem-based [50] Thermodynamics Computer based Drill-based [51] Thermodynamics Computer based Drill-based …”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Evans et al (2007) demonstrated that while learning through games, students developed positive attitudes regarding the environment besides they also behave in an environmentally responsible manner. Computer simulation games can be implemented in various teaching learning fields for promoting environmental awareness and exploring attitudes toward environmental conservation (Torres and Macedo 2000). Moreover, a recent study by Yang et al (2012) has shown that a digital game-based learning system can be used as a strategy to promote the selfawareness regarding energy conservation and enable learning energy conservation with higher motivation and willingness.…”
Section: Educational Computer Game and Gender Differencesmentioning
confidence: 99%
“…Using games as a teaching medium makes the learning process more enjoyable, which in turn makes the learners more receptive to the messages or information the game's creator or the instructor intends to convey [27].…”
Section: Overview Of Game-based Learningmentioning
confidence: 99%
“…In recent years, there has been a growing trend toward the use of games as a teaching method. Previous studies have revealed that the application of games in various practical teaching fields has achieved positive results [25][26][27]; for example, using games as a teaching medium has been shown to make the learning process more enjoyable, which in turn makes learners receptive to the learning content [27]. The game process is also a self-regulated learning model, meaning that it promotes individual cognitive development more effectively than traditional lecture-based learning [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation